2010
DOI: 10.7589/0090-3558-46.1.33
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Deerpox Infection in Black-Tailed Deer (Odocoileus Hemionus Columbianus)

Abstract: ABSTRACT:The pathogenic potential of deerpox virus was investigated via an experimental study utilizing seven black-tailed deer fawns (Odocoileus hemionus) between June and August of 2007. Successful transmission was achieved via intracutaneous and intravenous routes, and by commingling an uninoculated animal with experimentally infected fawns. One fawn became depressed and reluctant to eat but systemic clinical signs in the other fawns were confined to mild transient pyrexia. Typical multifocal poxviral cutan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
13
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 10 publications
0
13
0
Order By: Relevance
“…These are similar to lesions observed in black-tailed deer 6 to 8 days after cutaneous inoculation with DPV. 6 Chronic lesions of moose calves were histologically characterized by serocellular crust, epidermal regeneration, large numbers of lymphocytes and plasma cells, and a moderate number of macrophages with occasional multinucleated giant cells infiltrating the dermis, follicle, and adnexal glands. As with subacute lesions, these features were similarly observed 11 to 13 days after experimental cutaneous inoculation of DPV in black-tailed deer.…”
Section: Discussionmentioning
confidence: 99%
“…These are similar to lesions observed in black-tailed deer 6 to 8 days after cutaneous inoculation with DPV. 6 Chronic lesions of moose calves were histologically characterized by serocellular crust, epidermal regeneration, large numbers of lymphocytes and plasma cells, and a moderate number of macrophages with occasional multinucleated giant cells infiltrating the dermis, follicle, and adnexal glands. As with subacute lesions, these features were similarly observed 11 to 13 days after experimental cutaneous inoculation of DPV in black-tailed deer.…”
Section: Discussionmentioning
confidence: 99%
“…A titer of 1:2 or greater was considered positive. Serum samples from experimentally infected BTD fawns that developed clinical disease (Bildfell et al, 2010) Adult deer were more likely to be DPV antibody-positive (58/131; 44%) than juveniles (9/33; 27%), but again this association was not statistically significant (P50.11). Sera were obtained from many counties in Oregon and were grouped into four regions yielding these DPV antibodypositive serology values for Odocoileus spp.…”
mentioning
confidence: 89%
“…Alternatively, a low level of clinically apparent disease might reflect a pathogen of low virulence and the high antibody prevalence supports this view. An experimental study gave mixed results regarding DPV virulence; some animals developed only locally extensive and self-limiting lesions with minimal evidence of systemic effects, but one fawn developed a fulminate ulcerative mucocutaneous disease (Bildfell et al, 2010) similar to that originally described (Williams et al, 1985). A recently described DPV disease outbreak in captive WTD also caused death with extensive mucosal lesions in one fawn but only mild skin lesions in other exposed animals (Baughman et al, 2011).…”
mentioning
confidence: 96%
“…10,11 It has also been shown that experimental infection of black-tailed deer via intravenous or intracutaneous routes can induce clinical symptoms. 2 Phylogenic and morphologic characterizations of DPVs isolated from different host species located in various geographical regions indicate that these viruses are closely related. 8 In the current study, a report on the isolation of DPV from a white-tailed deer ( Odocoileus virginianus ) is documented.…”
mentioning
confidence: 99%
“…For virus isolation, tissue specimens, including skin, oral mucosa, and rumen, were processed as described previously. 2,8 In brief, tissue homogenates were inoculated onto primary testicular cells of black-tailed deer maintained in minimal essential medium a supplemented with 10% fetal bovine serum. b The inoculated cultures were examined daily for up to 7 days for cytopathic effect characterized by enlarged cytoplasm containing many inclusion bodies and cell detachment.…”
mentioning
confidence: 99%